GRASPING THE CULTURAL IDENTITY OF BLACKS AND WHITES IN TONI MORRISON’S SONG OF SOLOMON (A STUDY OF POSMODERNISM) - Supriyatno, Supriyatno (STKIP PGRI Jombang, 2018)
Grasping the cultural identity in a society is the characteristic and signifier to the existence and dimension of society in their life. The life of community in the broadest sense exists in paradigm of reflection and representation in the plots of norm, ideology, tradition and aesthetic involved in and it should not be the dichotomy in space and time in transferring the meaning of life. It is the forms of integrity, responsibility in orders of values, hope, ideals and futurThe research represents the life of human being in following, encouraging, accompanying, even fighting for how to reach the cultural identity in terms of rational and historical times. Colored with the problems of social stratification, race, and gender, this novel tries to convey the forms of paradoxical analyses and sharply elaborated in the structures of oxymoron in which imply on the studies of culture in a society to find out the self-identity. The analyses of the research are in the approach of post-modernism discussed as the reaction to the established modern era and its colors, meanwhile the data analyzed in terms of qualitative method with the techniques of interpretative qualitative in the steps of: data comprehensively read, interpretation of meaning and critical analyses.